(untitled) (Indonesian Journal of Agrarian Law, 2026)
National development projects, including the construction of the Cabean Reservoir in Blora Regency, Central Java, are part of the government’s efforts to realize social welfare and national food security. Behind these noble objectives, serious issues arise regarding legal protection for affected communities, particularly in the land acquisition process. This study aims to analyze the forms of legal protection for communities affected by the Cabean Reservoir construction project, identify occurring legal violations, and evaluate the effectiveness of available legal mechanisms. The research method employed is a juridical-normative approach coupled with qualitative analysis of laws and regulations, as well as primary data derived from interviews and field observations in Karanganyar and Todanan Villages. The findings indicate that despite the existence of a comprehensive legal framework—such as the Basic Agrarian Law (UUPA), the Law on Land Acquisition for Public Interest, and the Presidential Regulation on Social Impact Handling—field implementation frequently lacks transparency, fails to fulfill the principle of justice, and neglects the community’s right to fair compensation. Numerous residents reported unilateral land expropriation without proper consignment processes, land re-measurement, or valid documentation. This demonstrates a deficiency in both substantive and procedural legal protections. Therefore, it is imperative to strengthen oversight, foster community participation, and ensure consistent law enforcement so that national development does not compromise the rights of the citizens.